Profilaktyka muzyczna w pracy nauczyciela edukacji elementarnej = Prevention of music in the work of a teacher of elementary education - Kisiel, Mirosław (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article indicates that there is a need to promote among the teachers of elementary education the necessity of employing numerous musical form activities while working with children. The text stresses the value of prevention activities, in which music by providing specific content and emotions has a positive effect on different senses modeling human behavior. Conducting music classes in that way should be for children a source of joy, give them relaxation and stimulate their minds.
Keywords: profilaktyka muzyczna; dziecko; nauczyciele; edukacja elementarna; music prophylaxis; child; teacher; elementary education